Hepatoprotective Effect and Synergism of Bisdemethoycurcumin against MCD Diet-Induced Nonalcoholic Fatty Liver Disease in Mice - Kim, Sung-Bae (PLoS One, 2016)
Nonalcoholic fatty liver disease (NAFLD), the hepatic manifestation of the metabolic syndrome, has become one of the most common causes of chronic liver disease over the last decade in developed countries. NAFLD includes a spectrum of pathological hepatic changes, such as steatosis, steatohepatitis, advanced fibrosis, and cirrhosis. Bisdemethoxycurcumin (BDMC) is polyphenolic compounds with a diarylheptanoid skeleton, curcumin close analogues, which is derived from the Curcumae Longae Rhizoma. While the rich bioavailability research of curcumin, BDMC is the poor studies. We investigated whether BDMC has the hepatoprotective effect and combinatory preventive effect with silymarin on methionine choline deficient (MCD)-diet-induced NAFLD in C57BL/6J mice. C57BL/6J mice were divided into five groups of normal (normal diet without any treatment), MCD diet (MCD diet only), MCD + silymarin (SIL) 100 mg/kg group, MCD + BDMC 100 mg/kg group, MCD + SIL 50 mg/kg + BDMC 50 mg/kg group. Body weight, liver weight, liver function tests, histological changes were assessed and quantitative real-time polymerase chain reaction and Western blot analyses were conducted after 4 weeks. Mice lost body weight on the MCD-diet, but BDMC did not lose less than the MCD-diet group. Liver weights decreased from BDMC, but they increased significantly in the MCD-diet groups. All liver function test values decreased from the MCD-diet, whereas those from the BDMC increased significantly. The MCD- diet induced severe hepatic fatty accumulation, but the fatty change was reduced in the BDMC. The BDMC showed an inhibitory effect on liver lipogenesis by reducing associated gene expression caused by the MCD-diet. In all experiments, the combinations of BDMC with SIL had a synergistic effect against MCD-diet models. In conclusion, our findings indicate that BDMC has a potential suppressive effect on NAFLD. Therefore, our data suggest that BDMC may act as a novel and potent therapeutic agent against NAFLD.